Messianism and Kingship in the Gospel of John: A Comparison Between the Fourth Gospel and the Royal Psalms 2, 72, and 110 - Ryu, Gilsun (Journal of religious and theological information, 2017)
The article shows that messianism and kingship in the Gospel of John are involved in the royal psalms, such as Psalms 2, 72, and 110. Although these psalms were never quoted in the Gospel of John, there is a strong likelihood that the royal psalms have been alluded in the Gospel of John. This article examines the similarities and differences between the royal psalms and the Gospel of John, and, thus, shows how each present the messiah as the ideal king, concentrating on the terms "the Son of God," "the Son of man," and "the kingdom of God" that John shares with the royal psalms in terms of the messianic views. It appears that John uses the terms, in a unique way to emphasize the divine aspect of the messiah, by putting weight on the main characteristics of the messiah as the ideal king who was pre-existent before creation.